Composite materials based on graphene and zinc oxide nanoparticles - A. Ya. Shalyapina; A. Yu. Solovyova; M. A. Zaporozhets; E. M. Khokhlov; V. G. Plotnichenko; E. Yu. Buslaeva; E. G. Rustamova; S. P. Gubin (Тонкие химические технологии, 2012)
A method for obtaining zinc oxide nanocomposite on the surface of graphene flakes was developed. The resulting nanocomposites were characterized by a complex of research methods: transmission electron microscopy, X-ray phase analysis, and photoluminescence spectra.